2010
DOI: 10.1002/hep.23246
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Tenofovir Monotherapy for Hepatitis B Virus-Monoinfected Patients After Failure of Nucleoside/Nucleotide Analogues

Abstract: Tenofovir disoproxil fumarate (TDF) has demonstrated high antiviral efficacy in treatment-naive patients with chronic hepatitis B virus (HBV) infection but experience in nucleoside/nucleotide analogue (NA)-experienced patients is limited. In this retrospective multicenter study we therefore assessed the long-term efficacy of TDF monotherapy in patients with prior failure or resistance to different NA treatments. Criteria for inclusion were HBV DNA levels >4.0 log 10 copies/mL at the start and a minimum period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
264
3
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(290 citation statements)
references
References 24 publications
15
264
3
8
Order By: Relevance
“…64 As with any antiviral treatment that is taken in the long term, resistance is a concern, but tenofovir and entecavir have both so far demonstrated low rates of resistance. [65][66][67] The value of these drugs in supporting dentists who are chronic hepatitis B carriers and who wish to return to undertaking EPPs in dental practice is described later in this paper.…”
Section: Hbvmentioning
confidence: 99%
“…64 As with any antiviral treatment that is taken in the long term, resistance is a concern, but tenofovir and entecavir have both so far demonstrated low rates of resistance. [65][66][67] The value of these drugs in supporting dentists who are chronic hepatitis B carriers and who wish to return to undertaking EPPs in dental practice is described later in this paper.…”
Section: Hbvmentioning
confidence: 99%
“…In fact, TDF is less effective against mutant HBV strains containing the primary mutations associated with ADV resistance (rtA181T/V and/or rtN236T) in vitro (17). Patients with ADV-resistant HBV show an impaired response to TDF compared to patients without ADV resistance (22). More specifically, the rtA194T polymerase mutation has been found in HBV/HIV coinfected patients during TDF treatment, suggesting an association with TDF resistance (23).…”
Section: Tdfmentioning
confidence: 99%
“…There are some data from observational cohort studies suggesting that the efficacy of TDF is diminished in patients with ADV resistance (22,30). However, in a more recent randomized study comparing TDF or TDF + ETV in 102 patients with ADV-resistant chronic hepatitis B, both strategies were similarly effective (28).…”
Section: Adv Resistancementioning
confidence: 99%
“…With tenofovir treatment, the serum HBV DNA-negative conversion rate for patients without adefovir-resistance was 100%, but the rate was down to 52% for patients with adefovir-resistance [89] . An important feature of tenofovir is that tenofovir alone or with emtricitabine exerts an anti-viral effect to lamivudine, adefovir or entecavir resistance mutants [85,86,93,95,96] . For example, an article reported that for patients who achieved an insufficient effect by lamivudine, adefovir or the combination of these two drugs, tenofovir resulted in a serum HBV DNA-negative conversion rate of 79%, HBeAg-negative conversion rate of 24% and HBsAg-negative conversion rate of 3% of all patients (the median time from administration to HBsAg-negative conversion was 23 mo) [86] .…”
Section: Tenofovir Disoproxil Fumarate (Tenofovir)mentioning
confidence: 99%
“…An important feature of tenofovir is that tenofovir alone or with emtricitabine exerts an anti-viral effect to lamivudine, adefovir or entecavir resistance mutants [85,86,93,95,96] . For example, an article reported that for patients who achieved an insufficient effect by lamivudine, adefovir or the combination of these two drugs, tenofovir resulted in a serum HBV DNA-negative conversion rate of 79%, HBeAg-negative conversion rate of 24% and HBsAg-negative conversion rate of 3% of all patients (the median time from administration to HBsAg-negative conversion was 23 mo) [86] . For patients who achieved insufficient effect by lamivudine and adefovir, tenofovir alone or with lamivudine achieved a 64% serum HBV DNA-negative conversion rate 96 wk after changing therapy [93] .…”
Section: Tenofovir Disoproxil Fumarate (Tenofovir)mentioning
confidence: 99%